IMPROVING THE PROCESS OF TEACHING BIOLOGY BASED ON THE INTEGRATION OF NATURAL SCIENCES: A REVIEW OF EXPERIMENTS AND STUDIES - Mukhsinboyev Odilbek (Galaxy International Interdisciplinary Research Journal, 2024)
The article explores the issue of improving the process of teaching biology based on the mutual integration of the Natural Sciences. The processes of conducting pedagogical experiment work to test in practice the methodological support developed in this regard are highlighted. In improving the teaching of Science, the development of mental and practical activity skills of students, the importance of Natural Sciences in everyday life are analyzed.